(untitled) (Вісник Кримінологічної асоціації України, 2022)
The article is devoted to the study of the concept, essence, manifestations and legal signs of criminal offenses motivated by hatred. The opinion is defended that these offenses are socially dangerous, criminally illegal manifestations of discrimination, expressing intolerance, bias towards other people on the basis of nationality, race, religious, political views, gender, sexual orientation or any other features (indicators) of individual or group identity . In an extended aspect, in their mass, they can be understood as a cultural-psychological and socio-legal phenomenon, consisting in the existences of resentmentary, aggressive lack of freedom, sublimated in aggressively violent, discursively specific (hate speech)social practices of negative domination.